Uma abordagem territorial dos megaeventos esportivos em Belo Horizonte/MG: análise e interpretação do processo de desterritorialização dos antigos barraqueiros do Mineirão - Karla Trigueiro (2018)
International sport mega events are huge events that require high investments, with short-term durations and long-term consequences for host cities; directly interfering with the territorial dynamics, the flow of visitors and the organization of the tourist space, as well as the planning of large urban centers, with reverberation in the territorial experience of the local residents. Considering the complexity and repercussion of this phenomenon, this study intends to analyze the perception of the experiences of the actors of a certain group - directly involved with this type of event - with the objective of apprehending and understanding the perceived impacts through the deterritorialization of these actors. For this analysis, the focal group was chosen old barraqueiros of the Mineirão, for having an experience in the territory around the Governor Magalhães Pinto Stadium (Mineirão); in the period between the preparation, duration and finalization of the 2014 World Cup, held in several Brazilian cities, including Belo Horizonte. The approach was carried out, mainly, through the analysis of the speech and reports of the barraqueiros on the consequences suffered in their day to day, as a result of the accomplishment of this specific event. Thus, we intend to analyze the territorial experience of the actors directly affected, as a result of the international mega-events in the city of Belo Horizonte. The study evaluated the configuration of the territory - before and after the 2014 World Cup - the conflicts between the actors directly involved and the process of deterritorialization faced by them, through the different views of the chosen actors, from their place and role Social. As theoretical contributions, we rely on ethnogeography, through an ethnographic approach, based on the perception of those involved. Approaching the territory in dispute, we sought to understand the repercussions in the daily life of the people who receive the mega-events and / or who act in the organization and development of events of this nature. Having as a privileged geographic essence, the Territory, especially in an approach that privileges the perception of those involved, which constitutes a contribution of non-conventional analysis of processes linked to these phenomena. The results obtained were the rescue of the culture value, through the documents and reports of the group, and a historical record of the same was made, besides having provided, through theoretical contributions, the understanding of the process of deterritorialization experienced, in order to elucidate more perceptible data to this analysis, having, moreover, a character of originality because it is a humanistic view. The objective was to reflect on and expand the knowledge on the subject and the structuring of a theoretical contribution to the mitigation of these impacts, from the point of view of territory, territoriality and identity.